2009
DOI: 10.20965/jdr.2009.p0272
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Evaluation in a Flood Forecasting Model Using JMA Numerical Weather Prediction

Abstract: Numerical weather prediction (NWP) is useful in flood prediction using a rainfall-runoff model. Uncertainty occurring in the forecast, however, adversely affects flood prediction accuracy, in addition to uncertainty inherent in the rainfall-runoff model. Clarifying this uncertainty and its magnitude is expected to lead to wider forecast applications. Taking the case of Japan’s Shichikashuku Dam, 6 flood events between 2002 and 2007 were analyzed. NWP was based on short-range forecasts by the Japan Meteorologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…It is also based on the original tank, attributes with some physically based features 4) and nearly calibration-free parameters, because the model parameters have been internally calibrated using geo-topographical and land-surface information. In addition, the super tank model is semi-distributed, it is assumed to outperform lumped hydrologic models in terms of spatial variation consideration.…”
Section: (4) Hydrological Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also based on the original tank, attributes with some physically based features 4) and nearly calibration-free parameters, because the model parameters have been internally calibrated using geo-topographical and land-surface information. In addition, the super tank model is semi-distributed, it is assumed to outperform lumped hydrologic models in terms of spatial variation consideration.…”
Section: (4) Hydrological Modelmentioning
confidence: 99%
“…Recent studies demonstrated that the major source of model uncertainties is mostly induced by the NWP due to its intrinsic errors 4) . The forecast uncertainties are likely to be larger along with the forecast lead-time.…”
Section: (5) Model Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the precipitation will fall to the surface and become surface runoff, but some will be infiltrated through the soil layer and recharge the sub surface water. Surface run off is simulated by a two-dimensional shallow water equation while a NCF tank model [11] is applied at each grid of the domain. where u and v are the velocities in the corresponding axes, h is the water depth, q is the outsource term, and f S is the friction slope calculated with manning roughness ( n ) using eqns.…”
Section: Distributed Flood Modelmentioning
confidence: 99%
“…However, flood forecast models are subject to uncertainty in general, especially those are based on rainfall prediction obtained directly from the NWP model output. The errors in rainfall, even predicted by high resolution models, have been observed as the most significant contribution to the total model uncertainty (Kardhana and Mano [4], Xuan et al [5]). …”
Section: Introductionmentioning
confidence: 99%